Religious Manipulation: A Threat to Societal Development in Nigeria - Odo, Anselm Ikenna (Program Studi Sosiologi, 2021)
This paper sought to posit that religious manipulation is a threat to societal development in Nigeria. The researcher adopts descriptive method. Nigeria today has been known with a lot of diversity of belief which in one way or the other has a negative impact to the societal development. It is noticed that the diversity of religious practices in Nigeria is the outcome of manipulation. For a society to develop, tolerance is at times its fulcrum. The author concludes that intolerance and insurgency is as a result of religious manipulation. Which was as a result of poor checkmating of religious belief in Nigeria and to curtail it before it reaches to the worst stage. However, this paper recommends that in order to control this perilous act, there is a need for Nigeria to emulate on how to treat people irrespective of religion. And enhance peace education in Africa.